Conservative Management of a Splenic Artery Aneurysm in Pregnancy: A Case Report - Raleene Gatmaitan (Radcliffe Medical Media, 2020)
Splenic artery aneurysms (SAA) are a rare and life-threatening pathology. Ruptured SAA has a mortality rate of up to 25%, with increased rates of rupture in pregnancy, pseudoaneurysm, liver transplantation, portal hypertension, symptomatic SAA and diameter >2 cm. Management of SAA in pregnant women is poorly described in the literature, making treatment of these patients difficult. Furthermore, careful consideration of complications for both the mother and the foetus need to be taken into account. This case report demonstrates that conservative management with monthly surveillance MRI can be used as viable treatment option of an asymptomatic 17 mm splenic artery aneurysm in a pregnant woman.